Unmasking Human Metapneumovirus: The Emerging Threat to Vulnerable Populations - Alisha Arzoo (International Journal of Virus Studies, 2025)
Human Metapneumovirus (HMPV) is a contagious respiratory virus that commonly spreads among individuals. It can cause serious infections, especially in high-risk groups like infants, older adults, and individuals with weakened immune systems.It is a major contributor to acute respiratory illnesses. Since its discovery in 2001, HMPV has been identified as a common cause of both upper and lower respiratory tract illnesses, with clinical presentations ranging from mild symptoms to severe conditions like bronchiolitis and pneumonia. Accurate diagnosis relies on advanced laboratory techniques, including polymerase chain reaction (PCR) and antigen detection methods. Currently, treatment is primarily supportive, focusing on symptom relief and the prevention of complications, as no specific antiviral therapies or vaccines are available. Preventive measures emphasizing hygiene practices and respiratory etiquette are crucial in minimizing transmission. Continued research on vaccines and targeted treatments is crucial for better managing HMPV infections. This review explores various aspects of HMPV, including its history, structure, spread, how it causes disease, symptoms, diagnostic methods, and possible treatment options. By bringing together the latest information, it aims to emphasize HMPV’s impact on global respiratory health and the importance of ongoing efforts to develop effective prevention and treatment strategies.Human Metapneumovirus (HMPV) is a contagious respiratory virus that commonly spreads among individuals. It can cause serious infections, especially in high-risk groups like infants, older adults, and individuals with weakened immune systems.It is a major contributor to acute respiratory illnesses. Since its discovery in 2001, HMPV has been identified as a common cause of both upper and lower respiratory tract illnesses, with clinical presentations ranging from mild symptoms to severe conditions like bronchiolitis and pneumonia. Accurate diagnosis relies on advanced laboratory techniques, including polymerase chain reaction (PCR) and antigen detection methods. Currently, treatment is primarily supportive, focusing on symptom relief and the prevention of complications, as no specific antiviral therapies or vaccines are available. Preventive measures emphasizing hygiene practices and respiratory etiquette are crucial in minimizing transmission. Continued research on vaccines and targeted treatments is crucial for better managing HMPV infections. This review explores various aspects of HMPV, including its history, structure, spread, how it causes disease, symptoms, diagnostic methods, and possible treatment options. By bringing together the latest information, it aims to emphasize HMPV’s impact on global respiratory health and the importance of ongoing efforts to develop effective prevention and treatment strategies.
Keywords: Diagnosis and treatment; Human Metapneumovirus (HMPV); Preventive measures; Respiratory infections; Virus transmission